PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH KONFLIK KERJA TERHADAP KINERJA KARYAWAN - Sijabat, Asiani (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2024)
This study analyzes the effect of work conflict on employee performance embodied by job satisfaction. The sample used in this study amounted to 35 employees of PT. Mutiara Bakery Ambon. The technical analysis used is Partial Least Square (PLS). The results of this study showed that work conflicts did not have a significant effect on employee performance, The results also showed that work conflicts did not have a significant effect on employee satisfaction. Subsequently, job satisfaction has a significant effect on employee performance and the results show that job satisfaction mediates the influence of work conflict on employee performance